Web-based learning management system as media in teaching ESP for mathematics students in higher education - Abd. Syakur; Rizki Prasetya; Fajar Sandi Prawoco; Yulianto Sabat (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study examines the techniques used by ESP Math lecturers, the challenges they have in providing ESP learning materials, how they overcome these challenges, and the implications for ESP design. This study employed a qualitative research design by interviewing five ESP Mathematics lecturers teaching at STKIP PGRI Sidoarjo in the 2022-2023 academic year. 15 items of interview guidelines were prepared to gain a deeper understanding of what respondents have done in implementing the techniques of teaching ESP for Mathematics. The data were then examined using an interactive analysis process. The survey found that several of the lecturers had issues with vocabulary, pronunciation, grammar, and speaking fluency. The instructors overcame the obstacles by working together with other instructors and studying from printed and digital resources to better their command of the English language. Additionally, they utilized a web-based learning management system to aid in their education and facilitate the creation of instructional materials. It meant that the development of ESP for math educators had to concentrate on four areas: vocabulary, pronunciation, grammar, and fluency. The ESP curriculum might be developed using any number of platforms, including ones that cater to linguistics and mathematics.